Social Security Incentives in Belgium: An Analysis of Four Decades of Change - Anne-Lore Fraikin; Alain Jousten; Mathieu Lefèbvre (Institute of Labor Economics (IZA), 2018)
The paper traces labor market reforms over the last four decades. It provides estimates of retirement incentives for a selected set of typical worker profiles across time and socio-economic groups and links these series to the labor market performance in Belgium. The results show that the numerous retirement and social security program reforms have had a marked impact on incentives at the micro level. At the aggregate level, results are less clear-cut given the extreme diversity of programs and features in the Belgian institutional context.
Keywords: J21; J26; H31; I38; 330; retirement; social security; pension; labor supply